PENGARUH KONSENTRASI ASAM JAWA (Tamarindus indica L.) TERHADAP SIFAT FISIKOKIMIA DAN ORGANOLEPTIK LEATHER PULP KULIT PISANG KEPOK-ASAM JAWA - Purnomo, Lupita; Surjoseputro, Sutarjo; Setijawati, Erni (Widya Mandala Surabaya Catholic University, 2018)
Kepok banana (Musa paradisica L.) is a type of banana that is widely used for further processing. One part of banana that can be used is the peel. In banana peel there is a high enough of pectin (10-21%), therefore banana peel can be used as raw material on the leather. The fruit letaher is a thin sheet-shaped sweeter with a thickness of 2-3 mm, and has a water content of 10-25%. Fruit leather is good to have a slightly tough, compact texture also has a plasticity known by the gel system that is formed due to pectin, sugar and acids. Banana peel has a weakness, that is less attractive color (pale white) and it tasted bland, so on the making is necessary to add other materials, tamarind. Tamarind (Tamarindus indica L.) has a brownish- yellow flesh color and taste very sour. The sour taste is caused by tartaric acid, which is the main component of tamarind.This study aims to determine the effect of concentration on the physicochemical properties and organoleptic of kepok banana pulp-tamarind leather. The design of the study is a randomized block design (RAK) non-factorial with one factor and seven- level treatment, the concentration of tamarind written by 10%, 15%, 20%, 25%, 30%, 35%, and 40% with four replications. Kepok banana pulp- tamarind leather generated testing the water content, pH, texture (hardness), and organoleptic test covering the taste, texture and color. The test data will be analized using ANOVA (Analysis of Variance) at Î± = 5% and continued using Duncan Multiple Range Test (DMRT). The addition of tamarind increased the value of water content and texture (hardness), while the pH and color values (lightness, redness, and yellowness) decreased. The best concentration of tamarind was at 25%, which had pH 3,12, water content 11,79%, hardness 0,23 kg/s, lightness 42,33, Redness 17,61 and yellowness 23,33, and panelist sensory score of color (5,96), texture (5,94), and flavor (6,05) respectively with scoring 1-7.